Additions to the avifauna of the Banda Islands, Maluku - Lawrence Moores; Christopher Healey; Bas van Balen (KUKILA, 1996)
During a number of visits to the Banda Islands, which lie south of Seram in the Moluccas, the authors describe or refer to a total of 32 bird species that have not been recorded previously from the islands. The majority of these are migrant species or seabirds, while some others may have been introduced. Very few represent significant extension of breeding range. Future visitors are invited to pay particular attention to the goshawks and sunbirds